2022
DOI: 10.1002/anse.202200013
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Pretargeted Imaging of Tumors in Vivo

Abstract: Over the past decades, the pretargeted strategy has emerged as a promising approach to improve delivery of nucleotides into tumor tissues for nuclear imaging and/or therapy. Unlike conventional nuclear imaging and therapy, in which a radiolabeled tumor targeting vector (e. g., antibody) is directly administered and allowed to circulate and accumulate in the tumor tissues, the pretargeted strategy decouples the radiolabeled reporters with the targeting vectors; these two components could specifically couple thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Consequently, it was demonstrated that [ 68 Ga]­NOTA-SF-CV could be served as a feasible small-molecule PET tracer for sensitively and specifically monitoring cathepsin B activity in vivo . By combining the advantages of small-molecule probes and nanoprobes, the successful application of the tracer [ 68 Ga]­NOTA-SF-CV also demonstrated the applicability and universality of the SF scaffold designed by our group.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it was demonstrated that [ 68 Ga]­NOTA-SF-CV could be served as a feasible small-molecule PET tracer for sensitively and specifically monitoring cathepsin B activity in vivo . By combining the advantages of small-molecule probes and nanoprobes, the successful application of the tracer [ 68 Ga]­NOTA-SF-CV also demonstrated the applicability and universality of the SF scaffold designed by our group.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results have shown that stimuli‐triggered in situ self‐assembly is capable of prolonging the retention of small‐ molecule radionuclides in the tumor tissues, producing enhanced PET signals. [ 86–92 ] It is envisioned that stimuli‐controlled cascade in‐situ assembly and disassembly process may be adopted to design PET or SPECT imaging probes for sensitive imaging of multiple molecular targets or processes in vivo , benefiting to improve diagnosis of diseases. However, how to choose stimuli to sequentially control these complicated processes in vivo should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, Tz/TCO moiety accumulates at TOI through noncovalent high‐affinity interactions (e. g., antibody/peptide‐antigen recognition, streptavidin−biotin interaction, complementary oligonucleotide hybridization, etc. ), enhanced permeability and retention (EPR) effect, in situ self‐assembly, or covalent reactions [10,28] . In the second step, the signal agent is attached to the TOI via the Tz−TCO click reaction, or the signal agent is generated or released at TOI by the Tz−TCO click reaction, thus enabling the acquisition of the imaging signal at TOI.…”
Section: Design Principles For Imaging Probes Based On the Tz−tco Cli...mentioning
confidence: 99%
“…Bioorthogonal reactions, which can occur in living organisms without interfering with any biochemical processes or negatively affecting native biological activities, have evolved as highly useful tools for constructing imaging probes with high selectivity and high imaging contrast [9] . The combined use of pretargeted imaging and bioorthogonal reactions has proven highly efficacious in comprehending and manipulating biological processes [10] …”
Section: Introductionmentioning
confidence: 99%